Agar phantoms of biological tissue for fluorescence monitoring of photodynamic therapy. (January 2022) - Khilov, A V; Shishkova, V A; Sergeeva, E A; Kurakina, D A; Kirillin, M Yu
Abstract: An approach to fabricating agar phantoms mimicking spectral optical properties of biological tissues with fluorescent inclusions is proposed, which allows one to imitate the problem of optical visualisation of superficial biological tissues after the administration of a chlorin-based photosensitiser. The different arrangement of a fluorescent layer within a phantom makes it possible to simulate biological tissue in the cases of both topical application and intravenous injection of a photosensitiser. It is shown that absorption and scattering spectra of phantoms are in good agreement with the spectra of real biological tissues in the wavelength range of 500-800 nm. Changes in spectra of absorption and scattering coefficients of phantoms, as well as in their fluorescent properties induced by the addition of a fluorescent marker (chlorinbased photosensitiser) are demonstrated.